(untitled) (Ágora Journal, 2023)
This paper aims at highlighting the political importance of reporting practices in order to assure, in the international public opinion, the authoritarian and violent character of the Brazilian Dictatorship during the period from 1969 to 1974. Perceived as cultural practices, the reports demonstrate their political influence as the space in the international public opinion expands for its circulations, standing out representations that used to confront those widespread by the current Dictatorial Political Power in Brazil. For that matter, a symbolic struggle is configured about the Brazilian reality, in which Dictatorship sought to affirm itself by minting the representation “smear campaign against Brazil”. Through bibliographic studies and documents analysis produced by the Security and Information Department of the Justice Ministry (DSI-MJ), it was possible to verify that the Military Regime had succumbed to the paradoxes in which has been entangled, that is, to prove that was in fact an authoritarian and violent Dictatorship.